Preparing polycaprolactone scaffolds using electrospinning technique for construction of artificial periodontal ligament tissue - Safi, Ihab N. (J Taibah Univ Med Sci, 2020)
OBJECTIVES: The strategies of tissue-engineering led to the development of living cell-based therapies to repair lost or damaged tissues, including periodontal ligament and to construct biohybrid implant. This work aimed to isolate human periodontal ligament stem cells (hPDLSCs) and implant them on fabricated polycaprolactone (PCL) for the regeneration of natural periodontal ligament (PDL) tissues. METHODS: hPDLSCs were harvested from extracted human premolars, cultured, and expanded to obtain PDL cells. A PDL-specific marker (periostin) was detected using an immunofluorescent assay. Electrospinning was applied to fabricate PCL at three concentrations (13%, 16%, and 20% weight/volume) in two forms, which were examined through field emission scanning electron microscopy (FESEM). The isolated hPDLSCs were implanted on the fabricated PCL. After 21 days, FESEM was conducted to evaluate the implanted scaffolds, and an MTT assay was performed to characterize the biological response of the PCL scaffold at different cell exposure durations (24, 48, and 72 h). RESULTS: Periostin was expressed in the expanded PDL cells, and this result revealed that 20% weight/volume PCL scaffold with a pore size of more than 10 μm was the best. The growth rates of PDLSCs were high. Cytotoxicity test of fabricated PCL scaffold demonstrated no significant change in the cell viability when compared with the negative control and no deteriorating or inhibitory effect on growth after different durations. CONCLUSIONS: A cell sheet was successfully formed by using PCL as a scaffold to cover dental implants and promote PDL cell attachment, proliferation, and growth for biohybrid implant construction.